Analisis Manajemen Persediaan Obat Di Rumah Sakit Muhammadiyah Gresik Dengan Metode ABC dan EOQ - Ervianti, Oktavina; Kartika Sari, Ratna; Rachmadana, Divya (Journal of Economics and Business UBS, 2024)
This study aims to improve the efficiency of inventory management at Muhammadiyah Gresik Hospital through a descriptive qualitative approach by applying ABC analysis, and EOQ analysis. This method aims to identify, categorize, and optimize inventory management to increase productivity and reduce costs. First, ABC analysis is used to group inventory items based on their level of contribution to the total inventory value. The results of the study show the identification of goods that have a significant impact on availability and profitability. With this understanding, management can focus on key items that require special attention. Furthermore, EOQ (Economic Order Quantity) analysis is used to determine the optimal order quantity so that total inventory costs (order costs, storage costs, and inventory shortage costs) can be minimized. The implementation of EOQ helps avoid overstock or understock, improve operational efficiency, and optimize resource allocation. Related to the results of the research discussion conducted, the implementation of ABC analysis, EOQ is expected to increase operational efficiency, reduce inventory costs. This research provides a foundation for hospitals and similar health institutions to improve inventory management practices.